SINGULARITY AND THE LIMITS OF THE HUMAN SUBJECT: A KANTIAN PERSPECTIVE ON THE FUTURE OF ARTIFICIAL INTELLIGENCE. - Zhang, Zhiwu; Giordano, John (Prajñā Vihāra: Journal of Philosophy & Religion)
This paper discusses the issue of technological singularity and analyzes its far-reaching impact on the future of mankind in combination with Kant's transcendental philosophy. Technological singularity is often understood as the point at which artificial intelligence surpasses human intelligence, leading to discussions about human free will, ethics, and social structures. However, this paper argues that technological singularity is not necessarily a threat, but a natural result of human reason and technological innovation. Using Kant's critical philosophy, this paper considers artificial intelligence from the perspective of human motivation, moral responsibility, and the limits of the human subject. This paper aims to provide a framework for philosophical reflection on the technological singularity in order to promote a deeper understanding of the relationship between technology and humanity